Editorial: Boosting positivity by utilizing spirituality as a tool for recovery: Post-pandemic process - Baykal, Elif; Bhatti, Omar Khalid; Farooq, Waqas (Frontiers Media SA, 2023)
As a result of the COVID-19 pandemic, people were confronted with several drastic experiences that led to fear and uncertainty. In traumatic times like the COVID-19 pandemic, spirituality can act as a healing agent for the immune system, helping to promote mental health and pave the way for a more positive psychological state. Many researchers in positive psychology argue that one of the most important roles of spirituality is to promote greater peace of mind and reduce anxiety (Arslan and Yildirim, 2021; Baykal, 2022)
Keywords: Spiritual/Religious Coping; Spirituality; Pandemic (COVID-19); Recovery; Positive Psychology